Studies in the Pentateuch - Emerton, John Adney. (Supplements to Vetus Testamentum, 1990)
This collection of thirteen articles in English by scholars from several countries concerns questions in the Pentateuch. Seven are on the book of Genesis: the use of 'ādām in Genesis i-v; the Toledot of Adam; Genesis x in the light of Babylonian geography; the site of Salem; the date and composition of Genesis xiv; Abraham's righteousness in Genesis xv 6; the Hagar tradition in Genesis xvi and xxi. Three are on Deuteronomy: \'Yahweh is one\'; return to Egypt in Deuteronomy xvii 16 and xxviii 68; the creed in Deuteronomy xxvi. There are also essays on the Elohistic depiction of Aaron; the wilderness itineraries and recent archaeological research; and the dietary laws of the Pentateuch. Substantial contributions are made to the study of different parts of the Pentateuch.